Transient Enhanced GluA2 Expression in Young Hippocampal Neurons of a Fragile X Mouse Model - Banke, Tue G.; Barria, Andres (Frontiers in Synaptic Neuroscience, 2020)
AMPA-type glutamate receptors (AMPARs) are tetrameric ligand-gated channels made up of combinations of GluA1-4 subunits and play important roles in synaptic transmission and plasticity. Here we have investigated the development of AMPAR-mediated synaptic transmission in the hippocampus of the Fmr1 knock-out (KO) mouse, a widely used model of Fragile X syndrome (FXS). FXS is the leading monogenic causes of intellectual disability and Autism Spectrum Disorders and it is considered a neurodevelopmental disorder. For that reason, we investigated synaptic properties and dendritic development in animals from an early stage when synapses are starting to form to adulthood. We found that hippocampal CA1 pyramidal neurons in the Fmr1-KO mouse exhibit a higher AMPAR-NMDAR ratio early in development but reverses to normal values after p13. This increase was accompanied by a larger presence of the GluA2-subunit in synaptic AMPARs that will lead to altered Ca2+ permeability of AMPARs that could have a profound impact upon neural circuits, learning and diseases. In accordance with this, we found that young KO animals lack long-term potentiation, a well understood model of synaptic plasticity necessary for proper development of circuits and exhibit an increased frequency of spontaneous miniature excitatory postsynaptic currents, a measure of synaptic density. Furthermore, post-hoc morphological analysis of recorded neurons revealed altered dendritic branching in the KO group. Interestingly, all these anomalies are transitory and revert to normal values in older animals. Our data suggest that loss of FMRP during early development leads to temporary upregulation of the GluA2 subunit and this impacts synaptic plasticity and altering morphological dendritic branching.